Letter from Emil Brusewitz to James Curtis Booth - Brusewitz, Emil (1886)
Emil Brusewitz, a Swedish smelter, writes to James Curtis Booth (1810-1888) to discuss smelting techniques. Brusewitz thanks Booth for A History of the United States Mint and sends him a photograph of the Swedish royal palace as a gift. Photograph is not included in this collection.
Keywords: Booth, James Curtis, 1810-1888; Smelting; United States Mint; Mint of the United States